Unexpected polymorphism during a catalyzed mechanochemical Knoevenagel condensation - Haferkamp, Sebastian; Paul, Andrea; Michalchuk, Adam A. L.; Emmerling, Franziska (Beilstein Journal of Organic Chemistry, 2019)
The transformation of a base-catalyzed, mechano-assisted Knoevenagel condensation of mono-fluorinated benzaldehyde derivatives (p-, m-, o-benzaldehyde) with malonodinitrile was investigated in situ and in real time. Upon milling, the para-substituted product was found to crystallize initially into two different polymorphic forms, depending on the quantity of catalyst used. For low catalyst concentrations, a mechanically metastable phase (monoclinic) was initially formed, converting to the mechanically stable phase (triclinic) upon further grinding. Instead, higher catalyst concentrations crystallize directly as the triclinic product. Inclusion of catalyst in the final product, as evidenced by mass spectrometric analysis, suggests this complex polymorphic pathway may be due to seeding effects. Multivariate analysis for the in situ Raman spectra supports this complex formation pathway, and offers a new approach to monitoring multi-phase reactions during ball milling.
Keywords: ball milling; C–C coupling; in situ; mechanochemistry; multivariate data analysis

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Stolle, A.; Szuppa, T.; Leonhardt, S. E. S.; Ondruschka, B. (Chem. Soc. Rev., 2011)

(untitled) - Andersen, J.; Mack, J. (Green Chem., 2018)

(untitled) - Hulvey, Z.; Furman, J. D.; Turner, S. A.; Tang, M.; Cheetham, A. K. (Cryst. Growth Des., 2010)

(untitled) - Chadwick, K.; Davey, R.; Cross, W. (CrystEngComm, 2007)

(untitled) - Nielsen, S. F.; Peters, D.; Axelsson, O. (Synth. Commun., 2000)

(untitled) - Kaupp, G.; Reza Naimi-Jamal, M.; Schmeyers, J. (Tetrahedron, 2003)

(untitled) - Kulla, H.; Greiser, S.; Benemann, S.; Rademann, K.; Emmerling, F. (Cryst. Growth Des., 2017)

(untitled) - Fischer, F.; Greiser, S.; Pfeifer, D.; Jäger, C.; Rademann, K.; Emmerling, F. (Angew. Chem., Int. Ed., 2016)

(untitled) - Caira, M. R.; Nassimbeni, L. R.; Wildervanck, A. F. (J. Chem. Soc., Perkin Trans. 2, 1995)

(untitled) - Štrukil, V.; Fábián, L.; Reid, D. G.; Duer, M. J.; Jackson, G. J.; Eckert-Maksić, M.; Friščić, T. (Chem. Commun., 2010)

(untitled) - Friščić, T.; Halasz, I.; Beldon, P. J.; Belenguer, A. M.; Adams, F.; Kimber, S. A. J.; Honkimäki, V.; Dinnebier, R. E. (Nat. Chem., 2013)

(untitled) - Gracin, D.; Štrukil, V.; Friščić, T.; Halasz, I.; Užarević, K. (Angew. Chem., Int. Ed., 2014)

(untitled) - Batzdorf, L.; Fischer, F.; Wilke, M.; Wenzel, K.-J.; Emmerling, F. (Angew. Chem., Int. Ed., 2015)

(untitled) - Kulla, H.; Haferkamp, S.; Akhmetova, I.; Röllig, M.; Maierhofer, C.; Rademann, K.; Emmerling, F. (Angew. Chem., Int. Ed., 2018)

(untitled) - Lukin, S.; Tireli, M.; Lončarić, I.; Barišić, D.; Šket, P.; Vrsaljko, D.; di Michiel, M.; Plavec, J.; Užarević, K.; Halasz, I. (Chem. Commun., 2018)

(untitled) - Trotzki, R.; Hoffmann, M. M.; Ondruschka, B. (Green Chem., 2008)

(untitled) - Trotzki, R.; Hoffmann, M. M.; Ondruschka, B. (Green Chem., 2008)

(untitled) - Haferkamp, S.; Kraus, W.; Emmerling, F. (J. Mater. Sci., 2018)

(untitled) - Rightmire, N. R.; Hanusa, T. P. (Dalton Trans., 2016)

(untitled) - Simone, E.; Steele, G.; Nagy, Z. K. (CrystEngComm, 2015)

(untitled) - El-Agrody, A. M.; Al-Omar, M. A.; Amr, A. E.-G. E.; Ng, S. W.; Tiekink, E. R. T. (Acta Crystallogr., Sect. E: Struct. Rep. Online, 2013)

(untitled) - Antipin, M. Y.; Nesterov, V. N.; Jiang, S.; Borbulevych, O. Y.; Sammeth, D. M.; Sevostianova, E. V.; Timofeeva, T. V. (J. Mol. Struct., 2003)

(untitled) - Belenguer, A. M.; Lampronti, G. I.; Cruz-Cabeza, A. J.; Hunter, C. A.; Sanders, J. K. M. (Chem. Sci., 2016)

(untitled) - Pearson, K. (London, Edinburgh Dublin Philos. Mag. J. Sci., 1901)

(untitled) - Hotelling, H. (J. Educ. Psychol., 1933)

(untitled) - Casassas, E.; Marqués, I.; Tauler, R. (Anal. Chim. Acta, 1995)

(untitled) - Timofeeva, T. V.; Nesterov, V. N.; Antipin, M. Y.; Clark, R. D.; Sanghadasa, M.; Cardelino, B. H.; Moore, C. E.; Frazier, D. O. (J. Mol. Struct., 2000)

(untitled) - Haferkamp, S.; Fischer, F.; Kraus, W.; Emmerling, F. (Beilstein J. Org. Chem., 2017)

(untitled) - Hammersley, A. P.; Brown, K.; Burmeister, W.; Claustre, L.; Gonzalez, A.; McSweeney, S.; Mitchell, E.; Moy, J. P.; Svensson, S. O.; Thompson, A. W. (J. Synchrotron Radiat., 1997)